LESSONS LEARNED FROM SOCIAL MOBILIZATION PROCESSES IN COLOMBIA DURING 2021 - Bran Piedrahita, Lemy; Bran Piedrahita, Lemy; Bran Piedrahita, Lemy (Corporación Universitaria Americana, 2024)
The processes of social mobilization have been consolidated over the years as a crucial category of analysis within the social sciences, since they represent the manifestation of the emotions of individuals, which are usually linked to the expression of nonconformity with political, economic or social systems, depending on the catalysts that motivate people's mobility (Massal, 2021). Not surprisingly, with the advent of the 21st century, mobilizations have become increasingly frequent, using different means to organize people for a common cause -as has been the case of social networks since the strengthening of Information and Communication Technologies (ICTs)-. Consider, for example, the Arab revolts and the peasant strike in Colombia in 2013 (Massal, 2021).